2020
DOI: 10.1177/1369148120922808
|View full text |Cite
|
Sign up to set email alerts
|

Populist parties and foreign policy: The case of Italy’s Five Star Movement

Abstract: The role of political parties in foreign policy is gaining increasing attention. Nonetheless, despite an extraordinary interest in ‘populism’, the foreign policy of populist parties has rarely been investigated. This article provides an innovative theoretical framework, applying it on a rare example of a ‘pure’ populist party: Italy’s Five Star Movement. How has Five Star Movement positioned on Italian contribution to military operations abroad? What does such positioning say about its ideological leaning? In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Emanuele et al [18] found that "M5S voters are leftist on the economy but quite close to right-wing voters on Europe and immigration". This is reflected by some of the M5S press releases; for instance, they accused NGOs of increasing illegal immigration by rescuing migrants at sea [12]. These two parties, PD and M5S, formed a new government in August 2019, after Lega breached their governing coalition with Five Star Movement, hoping to trigger new elections [66].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Emanuele et al [18] found that "M5S voters are leftist on the economy but quite close to right-wing voters on Europe and immigration". This is reflected by some of the M5S press releases; for instance, they accused NGOs of increasing illegal immigration by rescuing migrants at sea [12]. These two parties, PD and M5S, formed a new government in August 2019, after Lega breached their governing coalition with Five Star Movement, hoping to trigger new elections [66].…”
Section: Related Workmentioning
confidence: 99%
“…pro-migration ads. 12 These ads, unlike those posted by political authors, are seen mostly by younger women. Thus, we find NGOs to assume a clear stance on the migration debate.…”
Section: Audience Demographicsmentioning
confidence: 99%
“…Finally, the picture is mixed as regard populist parties’ attitudes towards the use of force and intervening in other states’ internal affairs. In the realm of defence, their degree of support for military capabilities and solutions appear largely mediated by their thick ideologies and by national strategic cultures: for instance, most populist radical right party support higher defence spending while left-wing populist parties generally adopt pacifist postures, and while most populist parties tend to favour territorial defence, some support external force projection and military interventions against terrorist groups (Falkner and Plattner 2020 ; Coticchia and Vignoli 2020 ; Henke and Maher 2021 ; see also Wagner et al 2018 ).…”
Section: Populism and Foreign Policy: Theoretical Expectations And Research Tracksmentioning
confidence: 99%
“…Third, most of the scholarship on the foreign policy of governing populists has focussed on Latin America (Sagarzazu and Thies 2019 ; Wehner and Thies 2020 ; Wajner 2021 ), India (Plagemann and Destradi 2019 ; Wojczewski 2019a ), Turkey (Taş 2020 ) and, especially, the US (Drezner 2019 ; Wojczewski 2019b ; Hall 2021 ). Recent work on Europe has shed light on the foreign preferences of European populist parties (Liang 2007 ; Balfour et al 2016 ; Heinisch et al 2018 ; Coticchia and Vignoli 2020 ; Henke and Maher 2021 ) and how they have been projected at the EU level (Van Berlo and Natorski 2019 ; Futák‐Campbell and Schwieter 2020 ; Falkner and Plattner 2020 ) as well as on populist parties’ sovereignism more generally (see Basile and Mazzoleni 2020 ). By contrast, there has been little extensive analysis of the national foreign policies of European populist governments and how they have brought about changes of directions across policy areas (or not).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Italy, despite such growing debate over the Five Star Movement and Northern League, few analyses (Verbeek and Zaslove 2015;Balfour et al 2016;Coticchia and Vignoli 2020), have examined the foreign policy views of the two parties. However, a plausible common ideological feature emerges: their "domestic sovereignism" (Vittori 2017).…”
Section: Sovereignismmentioning
confidence: 99%